PENGEMBANGAN LANGKAH-LANGKAH PENGELOLAAN KELAS SECARA DARING UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR PESERTA DIDIK PADA MASA COVID-19 - Lailatussaadah; Hayati, Salma; Mardhiah, Ainul; Munawar (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
This study aims to develop a design for online classroom management measures to improve student learning discipline during the Covid-19 period. Data collection techniques in this study were documentation, interviews, observation and questionnaires. The subjects in this study were expert lecturers as experts, teachers and students as small group pilot tests. This research was conducted at SMAN Kembang Tanjong Pidie, Aceh in order to conduct a needs analysis and pilot test on a small group. The subjects of this research were 4 expert lecturers, 3 teachers 24 students in the needs analysis project and 10 students for the pilot test. The results showed that there were 8 forms of disciplinary action taken by students when online learning took place, this became the basis for developing online classroom management steps in order to improve student learning discipline. The results of the validation stage of the feasibility of the steps obtained a percentage of 82.63% with very decent criteria, the response of educators to the development of online classroom management steps was obtained 96.29%, with very good criteria, the results of the analysis of student responses obtained a percentage gain of 92.33% with very effective criteria. The assessment shows that the steps for managing online classes can be used as guidelines in improving student discipline.